The Effectiveness of the Peace Competency Program for Guidance and Counseling Teachers - Eva Imania Eliasa; Muh Farozin; Agus Basuki; Lintang Waskita Puri (Department of Guidance and Counseling, FIP, Undiksha, 2023)
The large number of Guidance and Counseling teachers who still need peace concepts and skills that are useful for themselves and the school has an impact on the lack of effectiveness of the guidance process given by teachers to students. So, this research was carried out to determine the program to increase personal competence at peace and identify the personal competence of peace teachers based on gender background, centrality, and length of working period. This research uses a quantitative type with a quasi-experimental approach to one group pre-post test design. The research subjects were 27 Guidance and Counseling Teachers. The research was divided into five stages using brainstorming, games, role-playing, cinema therapy, and assignment methods. Data collection used a questionnaire with the Teacher Peace Competency Development Scale instrument. The data analysis technique uses T-test analysis and simple regression. The research results show differences in peace competency from the knowledge and skills aspects, with a pretest of 51.74 and a posttest of 75.04. Then there is no difference in teacher gender in peace competency, but the average for male guidance and counseling teachers is higher than for female guidance and counseling teachers. The peace competency of BK teachers is the same from a background in the BK department and those who are not in the BK department, and there is a difference in the peace competency of BK teachers seen from the length of time they have worked. This research recommends that guidance and counseling teachers strengthen their knowledge and skills of peace to become personal role models of peace in their respective schools.